2017
DOI: 10.1001/jamapsychiatry.2016.3162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression in Patients With Mild Cognitive Impairment

Abstract: The prevalence of depression in patients with MCI is high. A contributor to heterogeneity in the reported literature is the source of the sample, with greater depression burden prevalent in clinic-based samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
262
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(301 citation statements)
references
References 109 publications
12
262
0
6
Order By: Relevance
“…As expected, those with MCI and dementia reported the highest prevalence of NPS (53.4% and 80%, respectively). This is consistent with previous reports of NPS in community-based samples of clinical groups, where NPS have been reported in 61%-97% of individuals with dementia [7,8] and 31%-50% of individuals with MCI [4][5][6]8]. These finding are or particular clinical relevance as it is well accepted that the comorbid presentation of NPS in MCI is linked to higher progression to dementia and that for patients with AD, NPS are associated with an increased likelihood of progression from mild to severe dementia [35].…”
Section: Prevalence Of Npssupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, those with MCI and dementia reported the highest prevalence of NPS (53.4% and 80%, respectively). This is consistent with previous reports of NPS in community-based samples of clinical groups, where NPS have been reported in 61%-97% of individuals with dementia [7,8] and 31%-50% of individuals with MCI [4][5][6]8]. These finding are or particular clinical relevance as it is well accepted that the comorbid presentation of NPS in MCI is linked to higher progression to dementia and that for patients with AD, NPS are associated with an increased likelihood of progression from mild to severe dementia [35].…”
Section: Prevalence Of Npssupporting
confidence: 93%
“…Prevalence estimates of NPS are reported among 31%-50% of individuals with MCI [4][5][6] and 61%-97% of individuals with dementia [7,8]. It is well accepted that the comorbid presentation of NPS in MCI is linked to higher progression to dementia [9][10][11][12][13][14][15] and that for patients with Alzheimer's disease (AD), NPS are associated with an increased likelihood of progression from mild to severe dementia [16].…”
Section: Introductionmentioning
confidence: 99%
“…1 Around half of those diagnosed with MCI will develop dementia within 3 years, and from the point of MCI diagnosis, 6% to 15% of patients will convert to dementia per year. 8,9 Nonetheless, the modifiable risk factors identified by Cooper et al are pathologies in their own right, with effective treatments available in primary care. Furthermore, a recent meta-analysis has shown that there are some modifiable predictors of conversion to dementia, including untreated diabetes and low dietary folate (with the caveat that there is currently no prospective evidence proving that modifying these risk factors reduces the risk of progressing to dementia, with the possible exception of folate supplementation).…”
Section: Introductionmentioning
confidence: 99%
“…NPS have been described in 79.5% of adults with MCI with worsening cognitive decline while depression was the most common manifestation 39. The overall prevalence of depression has been reported to occur in 32% of patients with MCI 40. The prevalence of anxiety among patients with MCI ranged from 14.3% to 31.2% 41.…”
Section: Definitions and Diagnostic Criteriamentioning
confidence: 99%